Factors Affecting Organizational Effectiveness in the Development Sector Organizations in Afghanistan - Ali, Shawkat (Pakistan Languages and Humanities Review, 2023)
This study investigates the factors affecting the organizational effectiveness in the development sector organizations in Afghanistan. The main objectives of the study are several folds including: Firstly, to investigate the effects of employee engagement on organizational effectiveness. Secondly, to examine the effects of employee retention on organizational effectiveness. Thirdly, to examine the effect of job satisfaction on org effectiveness The simple random sampling techniques is used to collect the data from the corresponding population. The sample of the study is 120 employees working in developmental sector organizations in Afghanistan. The ordinary least square estimation technique is used to assess the factors that affects the organizational effectiveness. The findings reveal that employee engagement, employee retention, and job satisfaction have a significant positive effects on organizational effectiveness. The study recommends that organizations should pay high attention toward satisfying, retention, and engaging the employees that would rises the organizational effectiveness.